SKRINING DAN UJI ANTAGONISME JAMUR TRICHODERMA HARZIANUM YANG MAMPU BERTAHAN DI FILOSFER TANAMAN JAGUNG - Efri, Joko Prasetyo, dan Radix Suharjo . (Universitas Lampung, 2009)
Screening and antagonism test of Trichoderma harzianum which are survived on the corn phyllosphere. The research was conducted to find Trichoderma harzianum that could survive on the corn phyllosphere which still have good antagonism capability. Five isolates T. harzianum were used in the research. Spore suspension of each isolate T. harzianum (108 spore/ml) was sprayed to the 21 days after planting corn phyllosphere in the afternoon. Reisolation in order to obtain the isolates which were was conducted in 1 – 22 days after spraying. To the extend that 3 isolates (from T. sprayed before harzianum) that could survive on the corn filosfeer and have the best antagonism capability then collected. Antagonism test was carried out using dual culture method. Phytophthora capsici was used as the antagonism object. The result showed that T. harzianum could survive until 22 days after spraying (DAS) on the last leaves (isolate 1, 2,3 and 5). On the second leaves, T. harzianum could survive 17 DAS Isolate 4 and 5) , and 20 DAS (isolate 5) on the meristem leaves. Antagonism test showed isolate 1 from reisolated from the last leaves (ThRI1), isolate 4 reisolated from the second leaves (ThDI4) dan isolate 5 reisolated from meristem leaves (ThTI5) were 3 isolates that have the best antagonism capability.